Getting a handhold on DNA: Design of poly-zinc finger proteins with femtomolar dissociation constants - Kim, Jin-Soo (The National Academy of Sciences, 1998)
Structure-based design was used to link zinc finger peptides and make poly-finger proteins that have dramatically enhanced affinity and specificity. Our studies focused on a fusion in which the three-finger Zif268 peptide was linked to a designed three-finger peptide (designated “NRE”) that specifically recognizes a nuclear hormone response element. Gel shift assays indicate that this six-finger peptide, 268//NRE, binds to a composite 18-bp DNA site with a dissociation constant in the femtomolar range. We find that the slightly longer linkers used in this fusion protein provide a dramatic improvement in DNA-binding affinity, working much better than the canonical “TGEKP” linkers that have been used in previous studies. Tissue culture transfection experiments also show that the 268//NRE peptide is an extremely effective repressor, giving 72-fold repression when targeted to a binding site close to the transcription start site. Using this strategy, and linking peptides selected via phage display, should allow the design of novel DNA-binding proteins—with extraordinary affinity and specificity—for use in biological research and gene therapy.